Anesthetic Management and Perioperative Care in Neonates with Esophageal Atresia: A Case Report - Adithya, Krisna Tri; Eko Setijanto (HM Publisher, 2024)
Introduction: Esophageal atresia is a congenital disorder that requires immediate surgical intervention. Careful anesthetic management and perioperative care are crucial for successful therapy in neonates with this condition. Case presentation: A 20-day-old male infant with esophageal atresia underwent anastomotic thoracotomy surgery. Premedication, induction, and maintenance of anesthesia were performed with a combination of Sevoflurane, Ketamine, and Fentanyl. Postoperatively, the baby was treated in the NICU with mechanical ventilation and antibiotic therapy. Conclusion: Comprehensive anesthetic management and perioperative care in neonates with esophageal atresia include prevention of aspiration, adequate ventilation, pain management, and close postoperative monitoring to ensure optimal outcomes.